IMMUNOINFLAMMATORY AND VASOACTIVE ENDOTHELIAL FACTORS AT THE PATIENTS WITH HELICOBACTER PYLORI – NEGATIVE GASTROPATHIES AND WITH A CHRONIC HEART FAILURE - Boiko, A. N. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The content of proinflammatory cytokine is increased in blood of the patients with helicobacter pylori – negative gastropathies and with chronic heart failure (CHF) of an ischemic genesis. This confirms the theory of existence of the system inflammatory answer at this category of patients. 105 patients with essential arterial hypertension and CHF of II and III functional classes with helicobacter pylori – negative gastropathies with the mediana of age 54 years were examined. It was established that degree of rising blood concentration of such cytokines as IL-1 and the TNF-a1 has direct dependence with stages of CHF. The analysis of the received results gave us the evidence that patients with CHF and helicobacter pylori – negative gastropathies have significantly higher levels of proinflammatory cytokines and ET-1 in comparison with patients without gastropathy. Also the blood level of PGFa1 was significantly smaller at this group. Thus, the development of gastropathy at the patients with arterial hypertension of 2 degree and with CHF is associated with activation of an immune inflammation and increasing disturbance of an endothelium functional condition. Significant differences at the patients with various level of cardiovascular risk were revealed only for the blood TNF-a1 content. This fact confirms the strong connection between this indicator and the forecast for the given category of patients.